The Effect of Changes in Tax Rates Amidst Tax Years in the Determination of Corporate Income Taxes in Ethiopia: A Comment on Federal Supreme Court Cassation Decision on ERCA v MIDROC Gold - Tesfay, Leake Mekonen (Bahir Dar University Journal of Law, 2023)
A dispute occurred between ERCA v MIDROC Gold (Federal Supreme Court Cassation Division, File No. File No. 130705, 07 Sep. 2017), because the mining tax rate was re-amended from 35% to 25% in 26 July 2013, bifurcating the tax year of 2013, creating an issue what should be the effect of the change in the tax rates amidst the tax year, particularly, whether these two tax rates can be applied in determining the latter’s profit taxes. The Federal Tax Appeal Commission, the Federal High Court, the Federal Supreme Court and the Cassation Division of the Federal Supreme Court decided that mining income taxes are paid on the aggregate annual taxable income not by dividing the year into months, and applied the new 25% tax rate for the aggregate annual taxable income. The author, in this work, disagrees with these decisions and argues that the times from 01 January to 25 July and from 26 July to 31 December should have been separately treated as transitional tax years; the 35% and 25% tax rates should have been applied to these transitional tax years respectively, and the annual tax should have been the summation. In this way, it was possible to avoid the undue retroactive application of the 25% tax rate, to strike a balance between the tax authority’s interest to collect due taxes and the taxpayer’s interest to pay taxes only due according to law, and moreover, to develop a precedent to avoid possible similar future controversies.